Predictors of treatment failure among pulmonary tuberculosis patients in Mulago hospital, Uganda - Namukwaya, E.; Nakwagala, F.N.; Mulekya, F.; Mayanja-Kizza, H.; Mugerwa, R. (African health sciences, 2011)
Early identification of Tuberculosis (TB) treatment failure using cost effective means is urgently needed in developing nations. The study set out to describe affordable predictors of TB treatment failure in an African setting. Objective: To determine the predictors of treatment failure among patients with sputum smear positive pulmonary TB at Mulago hospital. The study was carried out in the TB clinic of Mulago hospital Kampala, Uganda. This was an unmatched case control study where fifty patients with a diagnosis of TB treatment failure (cases) and 100 patients declared cured after completing anti TB treatment (controls) were recruited into the study. Cases were compared with controls to determine predictors of treatment failure. Results: Significant predictors of treatment failure in this study included a positive sputum smear at 2 months of TB treatment (OR 20.63, 95%CI 5.42- 78.41) and poor adherence to anti TB treatment (OR 14.59, 95%CI 3.04-70.15). Conclusion: This study identified a treatment related and a simple laboratory predictor of TB treatment failure in Mulago hospital which may be used in resource limited settings for early recognition of those at risk and early intervention.
Keywords: Predictors; Treatment failure; Pulmonary TB